Phenotypic correlates of serum neurofilament light chain levels in amyotrophic lateral sclerosis - Verde, Federico; Milone, Ilaria; Colombo, Eleonora; Maranzano, Alessio; Solca, Federica; Torre, Silvia; Doretti, Alberto; Gentile, Francesco; Manini, Arianna; Bonetti, Ruggero; Peverelli, Silvia; Messina, Stefano; et al. (Frontiers in Aging Neuroscience, 2023)
Objective To investigate the relationship between serum levels of the neuroaxonal degeneration biomarker neurofilament light chain (NFL) and phenotype in ALS. Materials and methods Serum NFL (sNFL) concentration was quantified in 209 ALS patients and 46 neurologically healthy controls (NHCs). Results sNFL was clearly increased in ALS patients and discriminated them from NHCs with AUC = 0.9694. Among ALS patients, females had higher sNFL levels, especially in case of bulbar onset. sNFL was more increased in phenotypes with both upper (UMN) and lower motor neuron (LMN) signs, and particularly in those with UMN predominance, compared to LMN forms. At the same time, primary lateral sclerosis (PLS) had significantly lower levels compared to UMN-predominant ALS (AUC = 0.7667). sNFL correlated negatively with disease duration at sampling and ALSFRS-R score, positively with disease progression rate, differed among King’s stages, and was negatively associated with survival. It also correlated with clinical/neurophysiological indices of UMN and LMN dysfunction (Penn UMN Score, LMN score, MRC composite score, active spinal denervation score). On the contrary, sNFL was not associated with cognitive deficits nor with respiratory parameters. Notably, we found a negative correlation between sNFL and estimated glomerular filtration rate (eGFR). Interpretation We confirm that ALS is characterized by increased sNFL levels, whose main determinant is the rate of degeneration of both UMNs and LMNs. sNFL is a biomarker of only motor, not of extra-motor, disease. The negative correlation with kidney function might reflect varying renal clearance of the molecule and deserves further investigation before introducing sNFL measurement as routine test in clinical care of ALS patients.